Overview of current pharmacotherapeutic options in benign prostatic hyperplasia - Koudonas, Antonios; Anastasiadis, Anastasios; Tsiakaras, Stavros; Langas, Georgios; Savvides, Eliophotos; Mykoniatis, Ioannis; Memmos, Dimitrios; Baniotis, Panagiotis; Vakalopoulos, Ioannis; de la Rosette, Jean J. M. C. H.; Dimitriadis, Georgios (Taylor and Francis Ltd., 2023)
Introduction: Benign prostatic hyperplasia (BPH) represents the histological entity of prostate cell proliferation, which inflicts a gradually increasing obstruction of the bladder outlet and is accompanied by a progressing manifestation of lower urinary tract symptoms (LUTS). BPH management algorithm includes conservative measures, pharmaceutical agents, and surgical procedures. Areas covered: A comprehensive literature review was performed using PubMed, Scopus, and Google Scholar databases to identify publications written in English, analyzing BPH pharmaceutical treatment. The search was conducted from January 2000 to January 2023. Six main drug classes can be administered, either as monotherapy or in combination. Furthermore, the authors provide current direction of research on future medications, which focuses on a more etiological interference to the BPH pathophysiological mechanism. Expert opinion: The available medications represent an effective first-line step of BPH/LUTS therapy. Currently, the administration of BPH medications is tailored to patient/disease characteristics and entails long-time adherence to therapy. The emergence of new surgical modalities, which combine significantly lower morbidity compared to standard procedures and more durable effects than the available medications, seems to challenge the current treatment algorithm. More direct comparisons and the increasing experience with these surgical modalities will delineate the switch points between various therapy levels along the BPH management sequence.
Keywords: Benign Prostate Hyperplasia; Bladder Outlet Obstruction; Drug Therapy; Lower Urinary Tract Symptomatology; Pharmacotherapy; Phytotherapy